Appendix 4.15: Marcos Diary Entry, 23 December 1972 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
In this entry, Marcos again vents his frustrations, this time against opposition politicians. He threatens (only privately, it seems) to postpone the ratification of the new constitution indefinitely, thereupon he would issue a decree that would reorganize the executive branch and effectively shut down congress indefinitely. He shows less antagonism toward the judiciary, though he laments that their sole concern—or so he claims—is security of tenure.